Shear strength characteristic of unsaturated undisturbed black volcanic ash soil in Kumamoto under static and cyclic loading - Okri Asfino Putra; Noriyuki Yasufuku; Adel Alowaisy; Ryohei Ishikura; Ahmad Rifa'i; Yuko Kawaguchi (International Association of Lowland Technology, 2020)
Black volcanic ash soil which is also known as Kuro-boku soil in Japan is a problematic type of soil. Kuro-boku is usually rich with allophane minerals, which are characterized by unique problematic properties. Through this paper, the shear strength and characteristics of the black volcanic ash soil collected at Kumamoto slope failure after earthquake 2016 were studied using three main approaches. The chemical composition of the black volcanic ash soil was investigated using the X-ray fluorescence analysis. Furthermore, the soil structure disturbance effect due to the earthquake shakes on the total shear strength was evaluated using a simple method that considers the pore size distribution that is reflected from the soil-water characteristic curve. In addition, the constant volume direct shear box considering static and cyclic tests were carried out. It was found that the main chemical content of the black volcanic ash soil is allophane which accounts for about 94 %. Furthermore, the undisturbed samples exhibit a unimodal pore structure, and the disturbed showed a bimodal pore. Since the pore structure of the disturbed sample is unstable, the static shear strength tends to be lower and the degradation index value is higher than that of the undisturbed sample.